(untitled) (UUM Journal of Legal Studies, 2022)
Malaysia’s counter-terrorism strategy has its roots within the 12-year campaign against the communist insurgency between 1948 and 1960. During the emergency period, the government relied heavily on executive-based measures, which operated as a primary instrument to execute the “Winning Hearts and Minds” agenda. The state executive body and its agents had a wide range of powers at its disposal, including indefinite detention without trial and the restriction of residence against terrorist suspects. A similar approach was maintained through various legislations, even after the country gained independence in 1957. However, recent developments indicate a significant change in the attitude of the government. The criminal justice approach begins to gain greater prominence, this being evident from the growing number of prosecutions against terror suspects and the creation of new terrorism-related offences. This paper first examines whether the apparent change is genuine and sustainable in the long term. This concern is connected with the nature and limits of the criminal law and justice system, along with other challenges derived from the existing structure, culture, and practices within the country. By adopting a socio-legal approach, this research also investigates the factors favouring and hindering the criminal justice approach empirically and theoretically as a primary legal response to countering terrorism in Malaysia. The ultimate aim is to contextualise an effective and fair legal response to terrorism that is able to operate within multifaceted counter-terrorism arrangements involving different stakeholders.